Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1053/jhep.2000.19322
|View full text |Cite
|
Sign up to set email alerts
|

The Hemodynamic Response to Medical Treatment of Portal Hypertension as a Predictor of Clinical Effectiveness in the Primary Prophylaxis of Variceal Bleeding in Cirrhosis

Abstract: In the prevention of variceal rebleeding, it is already established that hemodynamic response to drug treatment (decrease in hepatic venous pressure gradient [HVPG] to 12 mm Hg or by >20%) is predictive of clinical effectiveness. In primary prophylaxis very few clinical data are available. We assessed the role of the hemodynamic response to beta-blockers or beta-blockers plus nitrates in predicting clinical efficacy of prophylaxis. A total of 49 cirrhotic patients with varices at risk of bleeding, without prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
151
0
5

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 232 publications
(165 citation statements)
references
References 27 publications
9
151
0
5
Order By: Relevance
“…Decrease in HVPG to 12 mm Hg or less or decrease by at least 20% of baseline values is associated with low risk of variceal bleeding [47][48][49][50]. Poor hemodynamic response was found to be the main factor predicting bleeding.…”
Section: Recommendationsmentioning
confidence: 90%
See 3 more Smart Citations
“…Decrease in HVPG to 12 mm Hg or less or decrease by at least 20% of baseline values is associated with low risk of variceal bleeding [47][48][49][50]. Poor hemodynamic response was found to be the main factor predicting bleeding.…”
Section: Recommendationsmentioning
confidence: 90%
“…Assessment of hemodynamic response (decrease in HVPG to 12 mm Hg or less or decrease by at least 20% of baseline values) to drugs is the best predictor of efficacy of prophylaxis of variceal bleeding in patients treated with b-blockers or other portal pressure-reducing drugs [47][48][49][50][51][52].…”
Section: Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is logical to infer that the improved clinical outcomes reported with combination therapy reflect improved hemodynamics. Surprisingly, however, Merkel et al 4 found that those treated with ␤-blocker alone or with combination therapy were equally likely (ϳ60%) to have a good hemodynamic response. These findings are at odds with those of other studies 5 : the disparity may reflect differences in study populations.…”
mentioning
confidence: 98%